Application of nanofiltration for removal of zinc from industrial wastewater - Kočanová, Veronika; Cuhorka, Jiří; Dušek, Libor; Mikulášek, Petr (My University, 2017)
Wastewater treatment which deals with pollution by heavy metals, especially pollution of zinc is still the main issue in many industries. It is necessary to apply effective separation technology for pollutant substances that enter into wastewater. The aim of the present study is to test a commercially available nanofiltration membrane (AFC 40) for the separation of zinc sulphate from aqueous solutions. The major focus of this study is to investigate the influence of various operating conditions on the membrane performance. Thereafter, the AFC 40 nanofiltration membrane was employed for experiments on real samples of industrial wastewater containing zinc. Experiments with binary aqueous solutions were performed at various process conditions. Important parameters such as concentration of zinc, transmembrane pressure, pH range of the solutions and feed flow rate were studied. High values of rejection were achieved during all the experiments. The rejection of the AFC 40 membrane was measured for real samples of zinc-containing industrial wastewater. High value of rejection during the experiments with real samples of wastewater was achieved. During all the experiments with real samples of industrial wastewater, the achieved value of rejection was above 98%. The results obtained shows that the tested commercially available nanofiltration membrane (AFC 40) is suitable for the removal of zinc from both model binary solutions and real samples of wastewater.
Aplikace nanofiltrace pro odstranění zinku z průmyslových odpadních vod
Keywords: Heavy metal; Zinc; Nanofiltration; Těžké kovy; nanofiltrace; zinek